Unlocking ESG Premium from Options - Zhang, Weiming (Elaine); Cao, Jie; Goyal, Amit; Zhan, Xintong (Eunice) (SSRN, 2023)
We find that option expensiveness, measured by delta-hedged option returns, is higher for low-ESG stocks, indicating that investors pay a premium in the options market to hedge against ESG-related uncertainty. We estimate that this ESG premium is about 0.2% for 50 days. All three components of ESG contribute to option pricing. We find that investors pay the ESG premium to hedge against jump risks, but not volatility risks. The effect of ESG performance is more prominent during periods when attention to ESG is higher and for firms that are more subject to ESG-related risks.
Keywords: ESG; Risk premium; Delta-hedged option return; 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura